Contour analysis, a novel approach in movement science - van der Eb, J.; van den Tillaar, R.; Coolen, B. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Contour Analysis is a novel way for analyzing movements, which is specifically developed for daily use in high performance sports. The Contour Analysis is part of an automatic video capture and playback system, the CoachCockPit. Parameters like position, velocity and average body angle are obtained and also less straightforward parameters as step length or step frequency or 3D discus trajectory and speed can be investigated with Contour Analysis. The system is designed to operate fully automatic with a minimum of user input. Performance parameters obtained from the Contour Analysis can be used for direct feedback and to monitor progress over longer periods of time. To illustrate this several examples in different sports are discussed. The CoachCockPit is developed with primarily the coach perspective in mind: it does not interfere with daily training.